The application of interactive media design in searching for the events by using illustration / Nur Izzati Mohamed Rahaizah - Mohamed Rahaizah, Nur Izzati (2015)
The purpose of this research is to examine and analyses about The Application of Interactive Media Design in searching for the Events by Using Illustration. The main purpose will be focus on Interactive Illustration design for searching the events. In this discussion, we will examine how illustrations can attract attention, aid retention, enhance understanding, or create context. Plus, these will involving illustrations in the interactive media design. "Illustrations serve to expand, explain, interpret, or decorate a written text". This is taken from the article is taken from a doctoral candidate at Purdue University, in West Lafayette Indiana. Illustrations communicate people in many ways. The purpose why I choose The Application of Interactive Media Design is to try different ways instead of using text and words to inform and sending the message to people, why not using an illustration as a visual communication instead? It not only interactive but also can be used to as a visual presentation to draw attention to certain information.